Relationship Among Temporomandibular Dysfunction and Anxiety in the Students of the Fundamental Teaching - André Vinícius MARCHIORI; Alício Rosalino GARCIA; Paulo Renato Junqueira ZUIM; Aline Úrsula Rocha FERNANDES; Lígia Del'Arco Pignatta CUNHA (Association of Support to Oral Health Research (APESB), 2007)
Objective: With the objective of studying the temporomandibular dysfunction and anxiety levels in children, an epidemiological study was accomplished in scholars of the fundamental teaching of private schools of the Municipal District of Jaboticabal/SP. Method: For this study, 304 students were selected, being 83 of the 4th series, 117 of the 6th series and 104 of the 8th series (Committee of Ethics in Research: 200501873). The sampling was composed by children of both gender, with age among of 9 to 15 years. The evaluation was done by means of three self-applicable questionnaires: one to quantify the degree of temporomandibular dysfunction (Index of Fonseca), and two to determine the anxiety level (IDATE): Anxiety-State ("As I am feeling") and Anxiety-Trait ("Like me I generally feel"). The Anxiety-State questionnaire indicates as the children fells in a certain moment. The Anxiety-Trait questionnaire determines how the children generally fells during its lives. Results: The obtained data were tabulated and it allowed to arrive the following average scores of Index of Fonseca, Anxiety-State and Anxiety-Trait: 25.61 (13.25); 31.35 (5.03) and 38.61 (5.29), respectively. Conclusion: It was concluded that a great part of children's of fundamental teaching showed signs and symptoms of TMD and presented themselves quite anxious. Besides, analysis of data showed that a positive correlation exists between temporomandibular dysfunction and anxiety (p<0.01), mainly when comparing Trace anxiety, which is strongly related with personality.